2010
DOI: 10.1108/03074351011081286
|View full text |Cite
|
Sign up to set email alerts
|

The persistence of earnings and earnings components after the adoption of IFRS

Abstract: PurposeThis paper seeks to examine the persistence of earnings and earnings components after the adoption of International Financial Reporting Standards (IFRS).Design/methodology/approachThe study analyses two years before and two years after the adoption of IFRS in order to examine whether the adoption of IFRS materially affects the persistence, as well as the explanatory power of earnings and earnings components.FindingsThe results confirm that disaggregating reported earnings into operating income, non‐oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 34 publications
3
34
0
1
Order By: Relevance
“…Kabir, Laswad, and Islam () found evidence of increased earnings management in the post‐IFRS adoption period in New Zealand. Similarly, Doukakis () found that the mandatory adoption of IFRS in Greece did not result in any change in earnings persistence or the information content of earnings.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Kabir, Laswad, and Islam () found evidence of increased earnings management in the post‐IFRS adoption period in New Zealand. Similarly, Doukakis () found that the mandatory adoption of IFRS in Greece did not result in any change in earnings persistence or the information content of earnings.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Management incentives and national institutional factors play more important roles in reporting quality. Doukakis [44] analyzed whether the adoption of IFRS materially affects the persistence, as well as the explanatory power of earnings and earnings components of two years before and two years after the adoption of IFRS in Greece and confirmed that disaggregating reported earnings into operating income, non-operating income and extraordinary charge and credit, captures differences in the information content of the underlying events thereby earnings disaggregation can be used to improve prediction of future profitability. The results reveal that IFRS measurement and reporting guidelines do not appear to improve the persistence of earnings and earnings components.…”
Section: Ifrs Adoption and Earning Managementmentioning
confidence: 95%
“…Researchers showed that the standard IFRS, due to their principles, reduces the opportunist practices of the earning management. (Barth et al, 2008;Iatridis, 2010;Dimitropoulos et al, 2013;Doukakis, 2010). On the other hand, other researchers showed that the flexibility inherent in IFRS might provide greater opportunities for firms to manage earnings (Lin et al, 2012).…”
Section: Conclusion and Future Research Directionsmentioning
confidence: 98%